A Revolução Verde na mesorregião noroeste do RS (1930-1970) - Alves, Clovis Tadeu (2013)
This paper aims to make a historical analysis of the Green Revolution and economical in Brazil, emphasizing the changes occurring in agriculture mesoregion Northwest Rio Grande do Sul The study is justified by the historical relevance of the theme to the middle region in question, where the Agriculture was the first and main form of economic activity and the changes occurring in it changed the whole economic system, social and agrarian. Later modernizing movement started with the Green Revolution in mesoregion Northwest Gaucho extended to other agricultural areas of the country, impacting directly across the Brazilian agriculture. Thus, the paper aims to demonstrate how occurred the formation and consolidation of agricultural modernization program, represented by the Green Revolution in mesoregion Northwest, and the principle of dissipation model for other regions of the country, analyzing the period encompassing the 1930 to 1970.Although the study makes allusion in the first chapter on the international geopoliticalevents that have marked and influenced the training program of the Green Revolution in the global scenario. And in the second chapter makes a survey of relations and political actions in trame national and international, that influenced the adoption of the Green Revolution as a model for Brazilian agriculture. The work devoted special attention to the training (before the Green Revolution) of agriculture in Northwest mesoregion and the process of consolidation and modernization (Green Revolution) mesorregional agriculture. Within an analytical perspective, the Green Revolution was a product of the policies of technological dissemination sponsored by U.S. private institutions in order to create and developnew markets for agricultural technological products. Or served as a form of affirmation and capitalist in the Brazilian case and mesorregional as a way to internalize capitalist, turning the complex into a rural agroindustrial complex.